The Role of Halal Awareness, Halal Labels and Attitudes towards Halal Products on Purchase Decisions of Used Goods - Muhammad Rexsa Assyarofi; Muntafiah; Septian Agung Wijayanto; Fitri Wulandari (Al Tijarah, 2024)
The purpose of this study is to analyze the role of financial halal awareness, halal labels and attitude toward halal product on purchase decision. The sample of this research was residents of the city of Surakarta and its surroundings. Samples were selected using a non-probability sampling method totaling 200 respondents by distributing questionnaires online using Google Forms. The analysis technique used multiple linear regression supported by the SPSS program version 22.0. The results in this study show that there is a positive influence on Halal Awareness, and attitude toward halal product on purchase decision residents of the city of Surakarta and its surroundings whereas Halal Labels have no influence.